"As Much American as a Canadian Can Be": Cross-Border Experience and Regional Identity among Young Borderlanders in Canadian Niagara - Helleiner, Jane (Anthropologica, 2022)
This article analyzes interviews with young people who grew up on the Canadian side of the Canada-U.S. border in the Niagara region, a major North American transportation and trade corridor as well as a tourist destination. The analysis reveals histories of everyday cross-border links combined with some hybridized, but more often differentiating and exclusionary, constructions of border space and identity. Possible implications of these findings for official cross border regionalism and the wider project of North American deep integration are considered.